(untitled) (Research, Society and Development, 2022)
The objective of the present study is to identify the main care and interventions performed in cancer treatment for children diagnosed with cancer. It is a bibliographic survey and then a literature review. Conducted from January to April 2022 through a search in the Virtual Health Library (VHL), BDENF, Scientific Electronic Library Online (SciELO) and Latin American and Caribbean Literature on Health Sciences (LILACS) databases. The health descriptors used were: health team AND cancer treatment AND pediatrics. The inclusion criteria were: those published in any language as long as a translation is available, articles published in the period from 2018 to 2022 available for free, and in the databases mentioned above. In view of the findings, it was possible to identify 450 articles that, after applying the eligibility criteria and reading the rest, totaled 12 works used. The diagnosis of cancer is difficult to accept and brings with it feelings of hopelessness. It is an aggressive disease that requires specific treatment that requires interventions by health teams. Some care that can be performed are: palliative care, communication, offering a comfortable environment for the patient and their families, psychological support, among others. It is concluded that the health teams are directly linked to the care of children undergoing cancer treatment, as they have the knowledge and technical skills to provide this service.